STRATEGI PENGENDALIAN BIAYA DALAM MENINGKATKAN PROFITABILITAS PERUSAHAAN - Fadali Rahman; Putri Fatimah; Nauval Khair; Nuruddin; Ismi Fitri Aulia (Jurnal Riset Multidisiplin Edukasi, 2025)
This study discusses cost control strategies to improve company profitability through a literature review approach. Data were collected from scientific journals, financial management books, research articles, and company reports, then analyzed theoretically and comparatively to identify effective cost control strategies. The findings indicate that efficient use of raw materials, utilization of technology, elimination of non-value-added activities, structured budget management, and human resource optimization through training, competency placement, and incentive systems are able to reduce operational costs and increase profit margins. Cost control has a significant relationship with profitability improvement, as reflected by the increase in financial indicators such as ROA, ROE, and NPM. Therefore, cost control can be an essential strategy for companies to support financial stability and sustainable business growth.